Pengembangan Media Audio Visual Untuk Pembelajaran Maharah Istima’ Di Madarasah Tsanawiyah Al-Amiriyah Blokagung Banyuwangi - Mahbub Mahbub; Riska Khusnul (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
Listening skill is one of the four language skills (listening/istima, speaking/kalam, reading/qira'ah and writing/kitabah) that students learn for the first time before learning the other four language skills. Audio-visual media is an audio-visual aid which means materials or tools used in learning situations to assist written and spoken words in transmitting knowledge, attitudes, and ideas. This study used qualitative research methods. Where in this study will collect information related to the development of audio-visual media to increase maharah istima. The purpose of this study was to determine the development of audio-visual media to increase maharah istima' in learning Arabic, and to determine the increase in maharah istima' in learning Arabic. The technique used in this research is observation, interview, and documentation.